History of the Conditions and Political Situation of Kingdoms in Indonesia - Basri, Muhammad; Ginting, Febby Ardera Br; Alfiyalawati, Nia; Zahra, Andina (EDUCTUM: Journal Research, 2024)
The aim of this research is to examine the political conditions and situations that influence the Indonesian government. This research aims to examine the political conditions and situations that influence the Indonesian government. With a focus on political science, organizational structure, and inter-organizational relationships, this research uses a multidimensional approach to understand the evolution of policy between countries in the area of political science, organizational structure, and inter-organizational relationships. This research uses a multidimensional approach to understand the evolution of policy between countries in area. Using historical analysis, this research examines political evolution from the past to the present, identifying significant changes and key factors that influence the political system in each country. Political evolution from the past to the present, identifying significant changes and factors which influences the political system in each country. A comparative approach is used to compare political systems, power structures, and interactions between kingdoms, possibly identifying differences and similarities that influence political stability in various kingdoms. In addition, learning studies will provide deeper knowledge about the political dynamics that influence and shape government in Indonesia, as well as their implications for the country's political development. More in-depth knowledge about the political dynamics that influence and shape the Indonesian government, as well as their implications for political development country.